Pemanfaatan Sistem Informasi Manajemen Di SMK Negeri 2 Kota Bengkulu - Efi Eriyanti; Danim, Sudarwan (UNIVERSITAS BENGKULU, 2023)
The purpose of this study to describe (1) the use of software in managemen information system. (2) the use of hardware in management information system. (3) utilization of internet network in management information system (4) and user utilization of management information system. This type of research is descriptive qualitative research using a phenomenological approach. Data obtained from interviews, observations and documentation. Based on the data obtained in the study, it can be concluded that. (1) The Software uses specific application that have been determined and can be operated easily and has standards according to the insructions in the user manual. (2) The hardware in this sim is a computer that automatically connects to the internet quickly and is easy to use, can input, process, store and publish data in the form of relevant information from the results of data processing. (3) The internet network provides the information and knowledge we need and makes it easier for us to communicate with each other even remotely. (4) user, is a user of all management information systems, which processes, processes data and presents information